The spatial structures of Europe - Kincses, Áron; Nagy, Zoltán; Tóth, Géza (Acta geographica Slovenica, 2013)
Our study aims at describing the spatial structure of Europe with spatial moving average, potential model and the bidimensional regression analysis based on gravity model. Many theoretical and practical works aim at describing the spatial structure of Europe. Partly zones, axes and formations, partly polycentric models appear in the literature. We illustrate their variegation by listing, without any claim to completeness (since that could be the subject of another study), a part of them. Based on our examinations, the engraving of the structures that we described can be seen. The position of the core area of EU countries clearly justifies the banana shape and in relation to it, the catching up regions take shape in several areas.